(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The goal of this research which we intend to study passages of poems from the Experience of the Umayyad margin(Alsaealik), by describing the section of the poetic formation that dominated poems in that era, and the intention of studying the predicted connotations is to get the structure of those opening sections or it’s shrinking, this liberation was not only form wise. But it also indicated liberation in one way or another, from the culture of society established by the proof of primacy in general, because the overlooking speech, and Attributes, encodings, functions and symbols are expressed through the unique individual experience from moral cases for the groups. Therefor the new direction that was taken by the poetic sections in the Experience of the Umayyad margin, was an artistic and cultural reaction from the pioneers of that experience of what was happening, and it was meant to last, so they intended to rip live out of the frozen templates of expression that was ruled by tradition in the inherited poem, so that poetry become a form of life, starting from the present not the past which is connected to the collective memory, and Rooted in those beginnings, but still, what was left from the opening scenery in some section of the that experience is an image of what is left of the whole culture of the Umayyad society in General.